Characterization of poly(amic acid)s and resulting polyimides bearing azobenzene moieties including investigations of thermal imidization kinetics and photoinduced anisotropy. Issue 1 (4th June 2014) - Schab‐Balcerzak, Ewa; Skorus, Beata; Siwy, Mariola; Janeczek, Henryk; Sobolewska, Anna; Konieczkowska, Jolanta; Wiacek, Malgorzata
<x xml:space="preserve">Abstract</x> The aim was to develop new azobenzene polymers. For the first time, the photoinduced anisotropy in poly(amic acid)s (PAAs) was studied and compared with that in their polyimide (PI) analogues. <boxed-text content-type="graphic" id="pi4752-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>